1996
DOI: 10.2337/diacare.19.8.795
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HLA-DQB1 Genotyping for Four Alleles in the Assessment of Risk for IDDM in the Finnish Population

Abstract: The near-automatic typing procedure developed is attractive for large-scale screening projects, such as diabetes prevention and intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
2
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 27 publications
6
96
2
5
Order By: Relevance
“…Because this HLA-DQ2 molecule is also overrepresented in Type I diabetes, the frequent occurrence of coeliac disease in subjects with diabetes is believed to be connected with genetic predisposition [1]. In the Childhood Diabetes in Finland study, 43 % of children with diabetes and 24 % of population-based control subjects had the HLA-DQB1*02 allele [5]. Of the 427 non-diabetic siblings analysed in the present study, 29 % had HLA-DQB1*02.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Because this HLA-DQ2 molecule is also overrepresented in Type I diabetes, the frequent occurrence of coeliac disease in subjects with diabetes is believed to be connected with genetic predisposition [1]. In the Childhood Diabetes in Finland study, 43 % of children with diabetes and 24 % of population-based control subjects had the HLA-DQB1*02 allele [5]. Of the 427 non-diabetic siblings analysed in the present study, 29 % had HLA-DQB1*02.…”
Section: Discussionmentioning
confidence: 93%
“…The Childhood Diabetes in Finland study database was checked for cases of coeliac disease reported in questionnaires before the antibody screening. Genotyping of the HLA DQB1 locus was performed in 427 subjects by a PCR based hybridization assay using lanthanide labelled oligonucleotides and time-resolved fluorometry to detect the presence of Type I diabetes associated alleles [5].…”
Section: Methodsmentioning
confidence: 99%
“…HLA genotyping HLA was analysed on dried blood spots (DBS) on filters as described [28,29]. Filter samples (3 mm in diameter) of DBS were punched into 96-well PCR plates.…”
Section: Methodsmentioning
confidence: 99%
“…HLA The genotypes HLA-DQA1 and HLA-DQB1 were determined by PCR and sequence-specific probes as previously described [14,31,32]. HLA genotypes were available from 55 diabetic children, either from cord blood or from samples obtained at the diagnosis of diabetes.…”
Section: Control Childrenmentioning
confidence: 99%